The Importance of Using E-LKPD in Indonesian Language Learning - Mona Putri Maharani; Tressyalina; Afnita (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This research was conducted to find out the importance of using E-LKPD in learning Indonesian. This research was conducted using a qualitative approach, namely describing and elaborating information related to the importance of using the E-LKPD in learning Indonesian. The data collection technique in this study was library research, namely collecting data related to research variables, namely LKPD and Indonesian language learning obtained from books, scientific articles, proceedings, websites and other reliable literary sources. The results of this study are that the use of E-LKPD in learning Indonesian is very important. This is seen from analyzes of the needs of E-LKPD in schools. Some of the things that cause the use of E-LKPD are needed in learning Indonesian are the lack of student interest in learning, the need for teaching materials that are still lacking, especially in text-based learning, the lack of teaching materials for use in distance learning, and the need for teaching materials in accordance with the demands of the curriculum and technological progress is still lacking. In addition, from studies related to the development of E-LKPD it can also be seen that the E-LKPD resulting from this development is valid and practical to use. Thus, it can be concluded that the use of E-LKPD is very important in learning Indonesian.